To simplify \((6 - 3i)(3 - 5i)\) using the Distributive Property (also known as the FOIL method for binomials), we do the following steps:
-
First: Multiply the first terms:
\(6 \cdot 3 = 18\) -
Outer: Multiply the outer terms:
\(6 \cdot (-5i) = -30i\) -
Inner: Multiply the inner terms:
\((-3i) \cdot 3 = -9i\) -
Last: Multiply the last terms:
\((-3i) \cdot (-5i) = 15i^2\)
Since \(i^2 = -1\), this becomes \(15(-1) = -15\).
Now, combine all these results: \[ 18 - 30i - 9i - 15 \]
Combine like terms: \[ (18 - 15) + (-30i - 9i) = 3 - 39i \]
Thus, the simplified expression is: \[ 3 - 39i \]
The correct response is: 3−39i.